Visually cued fear conditioning test for memory impairment related to cortical function - Kazuya Kuboyama; Yuki Shirakawa; Koji Kawada; Naoki Fujii; Daiki Ojima; Yasushi Kishimoto; Tohru Yamamoto; Maki K. Yamada (Wiley, 2020)
Abstract Aim Fear conditioning tests are intended to elucidate a subject's ability to associate a conditioned stimulus with an aversive, unconditioned stimulus, such as footshock. Among these tests, a paradigm related to precise cortical functions would be increasingly important in drug screening for disorders such as schizophrenia and dementia. Therefore, we established a new fear conditioning paradigm using a visual cue in mice. In addition, the validity of the test was evaluated using a genetically engineered mouse, heterozygous deficient in Mdga1 (Mdga1+/‐), which is related to schizophrenia. Results Mice were given footshocks associated with a visual cue of moving gratings at training in 25‐minute sessions. The mice showed the conditioned response of freezing behavior to the visual stimulus at testing 24 hours after the footshocks. In the test for validation, the Mdga1+/‐ deficient mice showed significantly less freezing than wild‐type mice. Conclusion The visually cued fear conditioning paradigm with moving gratings has been established, which is experimentally useful to evaluate animal cortical functions. The validity of the test was confirmed for Mdga1‐deficient mice with possible deficiency in cortical functions.